Nghiên cứu thành phần hóa học dầu gan cá nhám góc Squalus japonicus Ishikawa - Truyền, Chu Quang; Ính, Cầm Thị; Hương, Hoàng Thanh; Latyshev, N. A.; Kasijanov, S. P.; Long, Phạm Quốc (Vietnam Journal of Chemistry, 2014)
A chemical investigation of the liver oil from the shark Squalus japonicus Ishikawa, collected in Quy Nhon bay led to the isolation of four compounds. Their structures were determined to be cholesterol (1), cholesteryl palmitate (2), palmitic acid (3) and 1-O-hexadecyl glycerol (4) by mean spectroscopic methods including ESI-MS, 1D- and 2D-NMR. Keywords: Squalus japonicus, Shark liver oil, Alkyl glycerols, Sterols.